Child Rearing, Risk, and Striving for Human Flourishing. Issue 4 (2nd April 2019) - Wolbert, Lynne; de Ruyter, Doret J.; Schinkel, Anders
Abstract: Parenthood can be characterized as a leap of faith; it is inevitably "risky." Here, Lynne Wolbert, Doret J. de Ruyter, and Anders Schinkel argue that this characterization of parenthood seems opposite to the current use of the concept of "risk" in contemporary educational theory and policy, which emphasizes that risk is something that is best prevented or avoided. Otto Friedrich Bollnow distinguishes between avoidable risks, on the one hand, and existential risks ( Wagnis ), on the other. The authors contend that Bollnow's description of education as a Wagnis (1) reinforces the understanding of child rearing and striving for flourishing as inherently uncertain; (2) contributes to a clarification of the ways in which the concept of risk is being used in educational theory and policymaking; and (3) leads us to recognize "trust" as a key concept in discussing risk taking and child rearing.